The Impact of Financial Ratios and Growth Opportunity on Capital Structure A Moderation Role of Firm Size - Gusfriyanto, Harri; Sihombing, Pardomuan (International Journal of Digital Marketing Science, 2024)
This study aims to examine the impact of liquidity, profitability, tangibility, and growth opportunity with firm size as a moderating variable on capital structure in distributor companies listed on the IDX Consumer Non-Cyclical for the period 2018-2022. The sampling technique used in this study was purposive sampling. The sample in this study consisted of 7 companies. This study uses panel data analysis techniques with moderated regression analysis (MRA) on E-views 13. Empirical results show that liquidity and profitability have a negative effect, and growth opportunity has a positive effect on capital structure, while tangibility does not affect capital structure. Firm size can only moderate growth opportunity to weaken the negative effect on capital structure, while tangibility cannot be moderated by firm size